Key distribution and recovery algorithm based on Shamir's secret sharing - Hui-gui RONG; Jin-xia MO; Bing-guo CHANG; Guang SUN; Fei LONG (Tongxin xuebao)
In Shamir's secret sharing scheme, the dealer divided the secret s into n shadows and distributed it to share-holders in such a way that any t or more than t shadows can recover this secret, while fewer than t shadows cannot obtain any information about the secret s. During the actual secret recovery process, there exist other cases with more than t par-ticipants. The case of secret sharing problem was discussed based on Shamir's secret sharing scheme and reconstructs the secret by introducing a linear combination of shadows—Lagrange factor. Then, the improved algorithm of key distribu-tion and recovery was proposed and extended to a multi-secret sharing scheme. Theoretical analysis and simulation show that the improved scheme improves its security under the same conditions of complexity.